Liberalisme Dalam Kajian Al-Qur’an (Study Pada Situs www.islamlib.com) - Fitri, Nanda Inka; Hakiki, Kiki Muhammad; Hendro, Beko (Pascasarjana Institut Ilmu Al Quran (IIQ) Jakarta, 2023)
Many Islamic controversies, especially regarding the ideas of the Liberal Islamic Network group, stem from human understanding, not from laws imposed by God. Opportunities like this often occur when religion is in human hands and resources are based on their own views and understanding abilities, therefore the purpose of writing this article is to examine the views of the Liberal Islamic Network (JIL) group towards the Al-Qur'an published through online media on the IslamLib website. Using analytical descriptive methods through a literature review, the author examines the views of the Liberal Islamic Network group regarding Human Rights (HAM), LGBT, Religious Pluralism, then analyzes them based on the Al-Qur'an approach and its rules of interpretation. The results of this research are to find out the meaning of Liberalism in the Al-Quran which is applied through the Liberal Islam website.